Identification of small peptides inhibiting the integrase‐LEDGF/p75 interaction through targeting the cellular co‐factor. (27th August 2013) - Cavalluzzo, Claudia; Christ, Frauke; Voet, Arnout; Sharma, Ajendra; Singh, Brajendra Kumar; Zhang, Kam Y.J.; Lescrinier, Eveline; De Maeyer, Marc; Debyser, Zeger; Van der Eycken, Erik
Abstract: The integration of the viral DNA into the host genome is one of the essential steps in the HIV replication cycle. This process is mediated by the viral enzyme integrase (IN) and lens epithelium‐derived growth factor (LEDGF/p75). LEDGF/p75 has been identified as a crucial cellular co‐factor of integration that acts by tethering IN to the cellular chromatin. Recently, circular peptides were identified that bind to the C‐terminal domain of IN and disrupt the interaction with LEDGF/p75. Starting from the circular peptides, we identified a short peptidic sequence able to inhibit the LEDGF/p75‐IN interaction at low μM concentration through its binding to the IN binding site of LEDGF/p75. This discovery can lead to the synthesis of peptidomimetics with high anti‐HIV activity targeting the cellular co‐factor LEDGF/p75 and not the viral protein IN. Copyright © 2013 European Peptide Society and John Wiley & Sons, Ltd. Abstract : In this work, we present the design, synthesis, and evaluation ofLP21, a short peptide that is able to inhibit the LEDGF/p75‐IN interaction at low μM concentration through its binding to the IN binding site of LEDGF/p75. Our discovery could lead to the synthesis of a peptidomimetic with high anti‐HIV activity targeting the cellular co‐factor LEDGF/p75 and not the viral protein IN.